Choices of Pre-service Elementary Mathematics Teachers’ Instructional Explanations: Division by Zero - Fatih Karakuş (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2017)
Besides having a strong subject-matter knowlege of mathematics teachers need to be expert in selecting and using appropriate examples and explanations so that they could facilitate their studnets’ understanding of mathematical concepts. Division by zero is a difficult topic to understand for both students and pre-service teachers. In this respect, it should be identified what kind of instructional examples and explanations are chosen by pre-service teachers related to division by zero. The aim of this study was to examine elementary pre-service mathematics teachers’ selection of instructional explanations in accord with the grade levels. Cross-sectional method was used. The reseach sample consisted of 197 pre-service teachers who were attending department of elementary mathematics education in an education faculty of a state university in Aegean region. Data were collected by a questionnaire, which was prepared by the researcher in the light of literature. Data was analyzed in a descriptive way; and Chi-squared test was used to determine how the participating teachers’ selection of explanations was changed according to grade level. Findings showed that irrespective of the grade level pre-service teachers preferred, mostly, concrete instructional explanations.